Electroplating sludge derived zinc-ferrite catalyst for the efficient photo-Fenton degradation of dye. (15th May 2017) - Cao, Zhenbang; Zhang, Jia; Zhou, Jizhi; Ruan, Xiuxiu; Chen, Dan; Liu, Jianyong; Liu, Qiang; Qian, Guangren
Abstract: A zinc-dominant ferrite catalyst for efficient degradation of organic dye was prepared by the calcination of electroplating sludge (ES). Characterizations indicated that zinc ferrite (ZnFe2 O4 ) coexisted with Fe2 O3 structure was the predominant phase in the calcined electroplating sludge (CES). CES displayed a high decolorization ratio (88.3%) of methylene blue (MB) in the presence of H2 O2 combined with UV irradiation. The high efficiency could be ascribed to the photocatalytic process induced by ZnFe2 O4 and the photo-Fenton dye degradation by ferrous content, and a small amount of Al and Mg in the sludge might also contribute to the catalysis. Moreover, the degradation capability of dye by CES was supported by the synthetic ZnFe2 O4 with different Zn to Fe molar ratio (n(Zn): n(Fe)), as 84.81%–86.83% of dye was removed with n(Zn): n(Fe) ranged from 1:0.5 to 1:3. All synthetic ferrite samples in the simulation achieved adjacent equilibrium decolorization ratio, the flexible proportioning of divalent metal ions (M 2+ ) to trivalent metal ions (M 3+ ) applied in the synthesis indicated that the catalyst has a high availability. Therefore, an efficacious catalyst for the degradation of dye can potentially be derived from heavy metal-containing ES, it's a novel approach for the reutilization of ES. Highlights: ZnFe2 O4 based catalyst was derived from the calcination of electroplating sludge. Efficient dye removal was achieved by photocatalytic process of CES-derived catalyst. Mg/Al coexistence in sludge enhanced the catalytic ability of Zn-Ferrite catalyst. The high availability provides a novel way to recycle the electroplating sludge.